2010
DOI: 10.1111/j.2042-3306.2010.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of sedatives, analgesic and anaesthetic drugs in the horse: An electronic survey of members of the American Association of Equine Practitioners (AAEP)

Abstract: Equine veterinarians can compare their choices of anaesthetic drugs with others practising equine medicine and surgery and may be stimulated to investigate alternative methods of providing comfort to horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…; Hubbell et al. ). Although blood pressure is usually well maintained under this and other similar injectable protocols (Young et al.…”
Section: Introductionmentioning
confidence: 98%
“…; Hubbell et al. ). Although blood pressure is usually well maintained under this and other similar injectable protocols (Young et al.…”
Section: Introductionmentioning
confidence: 98%
“…Butorphanol was the drug typically added to either α 2 agonist, when multiple drugs were utilized. The study found that acepromazine (alone or in combination) was the drug of choice for <1% of those who responded to the survey …”
Section: Discussionmentioning
confidence: 99%
“…Flunixin meglumine has been used in cats and pharmacokinetic data are available (Lascelles et al, 2007); however, with the availability of safer NSAIDs approved for use in cats its use cannot be recommended. Flunixin is one of the more commonly used NSAIDs in horses (Hubbell et al, 2010), and can be administered orally, intravenously, or intramuscularly. Cases of myonecrosis have been reported with intramuscular use (Peek et al, 2003).…”
Section: Flunixin Megluminementioning
confidence: 99%
“…Toxicity manifests as bone marrow suppression and gastrointestinal, renal, and hepatic injuries (Lascelles et al, 2007). The efficacy, availability, and affordability of phenylbutazone make it the most commonly used NSAID in horses (Goodrich & Nixon, 2006;Hubbell et al, 2010). It is available as parenteral and oral formulations.…”
Section: Phenylbutazonementioning
confidence: 99%